Armirani spajkani spoji povečane žilavosti - Zorc, Borut (Kovine zlitine tehnologije, 1997)
A mechanism of improvement of mechanical properties, of brazed joints by reinforcing is presented and confirmed. In all joints increased crack propagation reistance and toughness are observed. Two alternative ways of good joining of the armour and the base metal are described. An unconnected or weakly connected armour has practically no influence, while an appropriately joined armour and base metal in a joint show high tougness values of brazed joints.
Keywords: spajkanje; spajke; armature; žilavost; metalografske preiskave